Research Paper: Effect of Navayesh Parent-Based Comprehensive Rehabilitation Program on the Development of Early Language and Communication Skills in Deaf Children Aged 0-2 Years - Saeid Hassanzadeh; Fatemeh Nikkhoo (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective Early diagnosis and coherent rehabilitation programs play a key role in improving receptive and expressive language and communicational skills of deaf children. Communication with their parents could influence the development of languages and communication skills in these children. It is important to ensure parental involvement in the rehabilitation of deaf children as parent-therapists show the necessity for the provision of a comprehensive family-centered rehabilitation program along with the diagnosis of hearing loss and audiological and etiological evaluations. Materials & Methods This is an experimental study, with pre-test and post-test design. Sixty-two 0-2 years-old deaf children (30 girls and 32 boys), who either had undergone cochlear implant surgery or were candidates for cochlear implant surgery and had medical records at the Cochlear Implant Center in the Rasul Akram Hospital, were selected using purposive sampling. The subjects were then randomly divided into two groups (experimental and control groups). The subjects of the experimental group received the Navayesh parent-based comprehensive rehabilitation program in 18 group and individual sessions (6 group sessions and 12 individual sessions). To investigate early language and communication skills, the Ages and Stages Questionnaires, third edition, and the Communication and Symbolic Behavior Scales Developmental Profile were used. In addition, the Univariate and Multivariate Analysis of Covariance (MANCOVA) was used for the analysis of data. Results The findings of this study demonstrated that post-test average scores in communication skills increased in the experimental group compared to the control group with respect to pre-test (43.33). In addition, the MANCOVA results suggested that Navayesh comprehensive rehabilitation program was effective in increasing the scores in the areas of communication skills, expressive language, and symbolic behavior (P<0.001). Conclusion The results are indicative of the effect of the Navayesh parent-based comprehensive rehabilitation program on the development of early language and communication skills of deaf children. Therefore, it is recommended that this program should be used at rehabilitation centers for deaf children, aiming at training parents as the primary therapists of deaf children.